Peningkatan Kemampuan Komunikasi Matematis Siswa SMA/MA di Kecamatan Simpang Ulim melalui Model Pembelajaran Kooperatif Tipe STAD - Sahat Saragih; Rahmiyana – (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2013)
This research is aims to convinced: if the increase of students’ mathematical communication skills in through STAD cooperative learning is higher than those who taken direct learning and there is interaction between models of learning and increasing prior knowledge of students’ mathematical communication skills. This is an experimental research conducted in SMAN 1 Simpang Ulim and MAN Simpang Ulim with the population are all students in grade X of the schools which two classes from each school were randomly taken as samples. Two Ways ANOVA is applied to analyze the normalized gain of students’ conceptual understanding skills and mathematical communication skills. The results of this research showed that the increase of students’ mathematical communication skills through STAD cooperative learning is higher than those who took direct learning and there was not interaction between models of learning and prior knowledge the increase of students’ mathematical communication skills.ABSTRAK Tujuan penelitian ini untuk mengetahui tentang peningkatan kemampuan komunikasi matematis siswa yang mengikuti model pembelajaran kooperatif tipe Student Team Achievement Division (STAD), apakah lebih tinggi daripada siswa yang mengikuti model pembelajaran langsung dan ada interaksi antara model pembelajaran dan kemampuan awal matematika siswa terhadap peningkatan kemampuan komunikasi matematis siswa. Penelitian ini merupakan studi eksperimen di SMAN 1 Simpang Ulim dan MAN 1 Simpang Ulim dengan mengambil sampel 2 kelas dari masing-masing sekolah secara acak. Perolehan data ternormalisasi dianalisis dengan menggunakan uji ANAVA dua jalur. Hasil penelitian menunjukkan bahwa kemampuan komunikasi matematis siswa yang mengikuti model pembelajaran kooperatif tipe STAD lebih tinggi daripada siswa yang mengikuti model pembelajaran langsung, serta tidak ada interaksi antara model pembelajaran dan kemampuan awal matematika siswa terhadap peningkatan kemampuan komunikasi matematis siswa. Dengan demikian, model pembelajaran kooperatif tipe STAD dapat dijadikan sebagai salah satu alternatif model pembelajaran.